2011
DOI: 10.1016/j.jpeds.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hospitalizations for Patients Who Use a Structured Clinical Care Program for Children with Medical Complexity

Abstract: Objectives To describe the characteristics of hospitalizations for patients who utilize clinical programs that provide care coordination for children with multiple, chronic medical conditions. Study design Retrospective analysis of 1,083 patients hospitalized between June 2006 and July 2008 who utilize a structured, pediatric complex-care clinical program within four children's hospitals. Chronic diagnosis prevalence (technology assistance, neurologic impairment and other complex chronic conditions), inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
194
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 193 publications
(214 citation statements)
references
References 32 publications
11
194
0
9
Order By: Relevance
“…Our results are consistent with other researchers who found that neuromuscular conditions were common among children with CCCs and reports that the number of children with neurodevelopment disabilities has climbed over the past decade to nearly 1 in 6. 17,18 In addition, these children suffered from multiple CCCs. We found that more than 50% of the children had two or more CCCs, which was higher than Feudtner et al reported in their study of hospitalized children with CCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with other researchers who found that neuromuscular conditions were common among children with CCCs and reports that the number of children with neurodevelopment disabilities has climbed over the past decade to nearly 1 in 6. 17,18 In addition, these children suffered from multiple CCCs. We found that more than 50% of the children had two or more CCCs, which was higher than Feudtner et al reported in their study of hospitalized children with CCCs.…”
Section: Discussionmentioning
confidence: 99%
“…7 Health plans, children's hospitals, and other entities are enrolling high-cost children into care management programs to improve their health. 8 Some of these programs have reported a major impact on health care utilization and costs, suggesting that they may help interrupt the cycle of persistent health care spending that the children would have experienced otherwise. [9][10][11][12][13] As for their adult counterparts, 14 hospital care is a significant contributor to the overall cost accrued by children with chronic conditions.…”
mentioning
confidence: 99%
“…Although estimates indicate they account for <1% of the pediatric population, children with medical complexity and technology dependence use almost one-third of all pediatric health care expenditures and make multiple transitions across providers and health care settings. 1,3,6,7 For instance, in 2006, children with medical complexity accounted for 10% of all US pediatric acute care hospital admissions, www.hospitalpediatrics.org 26% of pediatric hospital days, 40% of pediatric hospital charges, up to 92% of technology assistance procedures, and 435 inpatient deaths. 7 It has become imperative for health care providers to study and understand the needs of this population as models of care are developed.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 More specifi cally, the 30-day readmission rate for children who are typically developing and without chronic illness is 3.1%. 3 For children with a single complex chronic condition and/or technology assistance, the rate of readmission to an acute care hospital has been reported to be up to 25% within 30 days of a previous hospitalization. 3,6 For children newly dependent on invasive mechanical ventilation and discharged from the hospital, the 12-month incidence of nonelective readmission has been reported at 40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation